Bridging the gap: wound healing in insects restores mechanical strength by targeted cuticle deposition - Parle, Eoin (J R Soc Interface, 2016)
If an insect is injured, can it repair its skeleton in a manner which is mechanically strong and viable? Previous work has described the biological processes that occur during repair of insect cuticle, but until now, there has been no biomechanical assessment of the repaired area. We analysed the biomechanics of the injury repair process in the desert locust (Schistocerca gregaria). We show that after an incision, a healing process occurred which almost doubled the mechanical strength of locust tibial cuticle, restoring it to 66% of the original, intact strength. This repair process occurred by targeted cuticle deposition, stimulated by the presence of the injury. The cut surfaces remained unrepaired, but a patch of endocuticle was deposited, reinforcing the area and thus increasing the effective fracture toughness. The deposition rate of endocuticle inside the tibia increased fourfold compared with uninjured controls, but only on the dorsal side, where the incision was placed. The limb is highly loaded during jumping, so this partial restoration of strength will have a profound effect on the fitness of the insect. A finite-element model provided insights into the mechanics of the repair, predicting that the patch material reaches its ultimate strength before the fracture toughness of the existing cuticle is exceeded.